Functional interplay of Epstein-Barr virus oncoproteins in a mouse model of B cell - Sommermann, Thomas; Yasuda, Tomoharu; Ronen, Jonathan; Wirtz, Tristan; Weber, Timm; Sack, Ulrike; Caeser, Rebecca; Zhang, Jingwei; Li, Xun; Chu, Van Trung; Jauch, Anna; Unger, Kristian; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Epstein-Barr virus (EBV) is a B cell transforming virus that causes B cell malignancies under conditions of immune suppression. EBV orchestrates B cell transformation through its latent membrane proteins (LMPs) and Epstein-Barr nuclear antigens (EBNAs). We here identify secondary mutations in mouse B cell lymphomas induced by LMP1, to predict and identify key functions of other EBV genes during transformation. We find aberrant activation of early B cell factor 1 (EBF1) to promote transformation of LMP1-expressing B cells by inhibiting their differentiation to plasma cells. EBV EBNA3A phenocopies EBF1 activities in LMP1-expressing B cells, promoting transformation while inhibiting differentiation. In cells expressing LMP1 together with LMP2A, EBNA3A only promotes lymphomagenesis when the EBNA2 target Myc is also overexpressed. Collectively, our data support a model where proproliferative activities of LMP1, LMP2A, and EBNA2 in combination with EBNA3A-mediated inhibition of terminal plasma cell differentiation critically control EBV-mediated B cell lymphomagenesis.
Gesehen am 09.09.2020